Участь бібліотек Західних Балкан у VIAF при створенні авторитетних файлів - Перенесієнко, Ігор (Видавництво Львівської політехніки, 2025)
The article explores the specifics of creating authoritative files related to the Western Balkans. The dynamics of the work of libraries in the region in this direction are analyzed. A review of resources is carried out in which biographical information and the specifics of cooperation with VIAF are thematically presented.
Keywords: Західні Балкани; авторитетні файли; бібліотечні каталоги; VIAF